Empowerment of women through entrepreneurial activities of self-help groups in Bangladesh - Akter, Aysha; Ahmad, Nobaya; Wan Jaafar, Wan Munira; Zawawi, Dahlia; Islam, Md. Monirul; Islam, Mohammad Ashraful (Research Publishing Academy, 2018)
The empowerment of women is a multidimensional process that enables them to realize their full identity and power in all spheres of life. One of the powerful approaches to achieve women’s empowerment is the formation of self-help groups (SHGs), especially among women. These groups support entrepreneurship development and incomegenerating activities that fit around the needs of homemakers and which, over time, can empower women. This study investigates the empowerment of rural women in Sylhet district in Bangladesh through their participation in the entrepreneurial activities of SHGs. Based on data gathered from 100 respondents, the findings show that taking part in the entrepreneurial activities of SHGs has a significant impact on uplifting the socio-economic empowerment of the Bangladeshi women. Based on the results, women must be further empowered by enhancing their awareness, knowledge, skills and technology usage, thereby facilitating the overall development of the society.